Pre-Service and in-service teachers' views of the sources of students' mathematical difficulties - (:unkn) unknown (My University, 2011)
This paper examines the views of pre-service and in-service teachers with regard to the sources of students' mathematical difficulties. A group of 40 pre-service mathematics, 15 in-service mathematics and 15 in-service elementary teachers participated in this study. Questionnaires are used as data collection tools to see what the participants think about the sources of student difficulties. The notion of "obstacles to learning" is used as a framework to analyze the collected data. The analysis is carried out on the basis of three main categories to which participant teachers attribute students' difficulties: epistemological causes, psychological causes and pedagogical causes. The data analysis reveals that both pre-service and in-service teachers tend to attribute students' difficulties to student-related factors, namely psychological causes. We discuss the findings in terms of these three sources of learning difficulties, educational implications and note the usefulness of the employing the "obstacles to learning framework" in examining not only students' learning difficulties but also Teachers' views of the sources for student difficulties.
Keywords: Obstacles to learning; Sources of students' mathematical difficulties; Teacher views